2020
DOI: 10.3390/w12061688
|View full text |Cite
|
Sign up to set email alerts
|

Nitrifying and Denitrifying Microbial Communities in Centralized and Decentralized Biological Nitrogen Removing Wastewater Treatment Systems

Abstract: Biological nitrogen removal (BNR) in centralized and decentralized wastewater treatment systems is assumed to be driven by the same microbial processes and to have communities with a similar composition and structure. There is, however, little information to support these assumptions, which may impact the effectiveness of decentralized systems. We used high-throughput sequencing to compare the structure and composition of the nitrifying and denitrifying bacterial communities of nine onsite wastewater treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 81 publications
0
11
0
Order By: Relevance
“…Wigginton et al [22] also found Nitrosomonas and Nitrosospira to be the most prevalent genera across both settings. Nitrosospira is most commonly found in soil environments, which suggests that these bacteria are likely introduced to OWTS through soil that enters treatment train components during the initial system installation as well as during periodic maintenance inspections [22,28]. The overlap in prevalent nitrifiers observed in OWTS between systems in the Wigginton et al [17,22] studies and those in our systems suggests that certain genera dominate the nitrification process in N-removal OWTS.…”
Section: Amoa: Taxonomymentioning
confidence: 88%
See 3 more Smart Citations
“…Wigginton et al [22] also found Nitrosomonas and Nitrosospira to be the most prevalent genera across both settings. Nitrosospira is most commonly found in soil environments, which suggests that these bacteria are likely introduced to OWTS through soil that enters treatment train components during the initial system installation as well as during periodic maintenance inspections [22,28]. The overlap in prevalent nitrifiers observed in OWTS between systems in the Wigginton et al [17,22] studies and those in our systems suggests that certain genera dominate the nitrification process in N-removal OWTS.…”
Section: Amoa: Taxonomymentioning
confidence: 88%
“…Although Wigginton et al [17] observed a higher number of ASVs (711) in samples from 38 advanced N-removal OWTS, they also identified Nitrosospira and Nitrosomonas as two of the most common genera present in effluent. Both genera have also been observed in BNR WTPs throughout the world [4,22,26,27]. Wigginton et al [22] also found Nitrosomonas and Nitrosospira to be the most prevalent genera across both settings.…”
Section: Amoa: Taxonomymentioning
confidence: 91%
See 2 more Smart Citations
“…2) indicateing that processes that produce N2O, such as nitrification and incomplete denitrification, take place to the same extent in both zones. Wigginton et al (2020) found that the structure and composition of communities of ammonia oxidizing and denitrifying bacteria in these two zones in nine advanced N-removal OWTS did not differ significantly, suggesting a similar potential for N2O production via these processes. As was the case for the other two gases, N2O flux was not influenced by home occupancy pattern, mirroring the fact that the structure and composition of the microbial communities of seasonal and year-round systems were similar (Fig.…”
Section: Nitrous Oxide Fluxmentioning
confidence: 92%